HOME DEATHS ARE MORE COMMON AT WEEKENDS AND HOLIDAY PERIODS AMONG CHILDREN AND YOUNG PEOPLE (CYP) WHO DIE FROM CANCER. Issue 1 (1st March 2014) - Gao, W; Verne, J; Davies, JM; Peacock, J; Gordon, E; Morris, C; Greenough, A; Higginson, IJ
Abstract : Introduction: Healthcare staffing and service levels during weekends and holiday (WH) periods are lower than other periods. It is unclear if such configuration plays a role in place of death (PoD) for CYP cancer deaths. Healthcare staffing and service levels during weekends and holiday (WH) periods are lower than other periods. It is unclear if such configuration plays a role in place of death (PoD) for CYP cancer deaths. Aim(s) and method(s): To evaluate the relationship between CYP cancer deaths during WH periods and PoD. 5, 432 CYP cancer deaths (≤24 years) in England in 2001–2010 were extracted from ONS death registration database. The outcome was PoD. WH periods were defined as Saturday or Sunday, two days before or after Christmas, and one day before or after New Year's Day or Easter. Results: Overall, 30% of CYP cancer deaths occurred in WH periods. Compared to other periods (47.7% [46.2–49.3%], there was a reduced proportion of deaths in hospital during WH periods (−3.5% [−6.4 to −0.6%]), and an increased proportion of home deaths during WH periods (3.5% [0.6–6.3%]). Deaths in other places remained stable regardless of period. Multivariate log-binomial analysis (adjusting for age, gender, cancer site, year of death and deprivation) confirmed that CYP cancer deaths were more likely to occur at home during WH periods than in other periods (PR: 1.06 [1.01–1.12], P=0.017). Conclusion(s): Relatively more CYP cancer deaths occurred at home during WH periods than in other periods, mirroring a decrease in hospital deaths. Further research is needed to understand the reasons for this pattern, particularly the roles of service users' preferences, service provision and care quality. Our results highlight a need for well co-ordinated community palliative and primary care support at WH periods.